GREEN BARRIER PT PUSRI POTENTIAL AS BIRD HABITAT - Sevli, Melto; Zulkifli, Hilda; Yustian, Indra (BIOVALENTIA: Biological Research Journal, 2016)
The study was conducted to determine birds in Green Barrier PT. Pusri and explains the function of the existing vegetation in the Green Barrier for many species of birds. Retrieval of data was conducted in a 28 ha Green barrier area of PT Pusri, during July to August 2015. The collecting of data determined by line transects through observation directly. assuming the selection of sites in the area of water resources and representation of vegetation types that represent a potential habitat for birds. Birds observed then identified and recorded the type, activity include, nesting, feeding, perch and plants that exploited. The results of this study found 17 species in 13 families. Plant species are most frequently used by birds is batai wood (Paraserianthes falcataria). Recorded at least 10 species of birds found in the Green Barrier PT. Pusri utilize these plants as a perch, feeding and nesting. The availability of water in the form of an artificial fish ponds at the fish pond 1 (transect 3) to attract water birds such as; Javan Pond-heron (Ardeola spesiosa) and Common Sandpipers (Tringa hypoleeucos) to come looking for food that needs to be managed to maintain its function as a habitat for birds.Keywords: Birds, plant, habitat, Green Barrier PT. Pusri.